Analisis Pengaruh Harga, Persepsi Ukuran, Persepsi Reputasi, dan Kualitas Layanan Terhadap Kepercayaan Konsumen Dalam Menggunakan Transportasi Online (Studi Kasus : GO-JEK Indonesia) - Muh. Edo Aprillia Andilala; Fitra A. Bachtiar; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
GO-JEK Indonesia is an online-based transportation with the most users in Indonesia with 21.6% users. Consumers have more trust in GO-JEK than any other online transportation services. One of the things to consider in choosing a product or service is price. In addition, perceived of size, perceived of reputation, and quality of services are considered to have positive influences on GO-JEK consumer belief. The problem arise is the influence between price, perceived of size, perceived of reputation and service quality with trust is not known. In addition, it is not known which variables are most influential on trust. Multiple linear regression is used to answer the problem. Primary data were obtained from questionnaires distributed online by social media. F test and T test are conducted to know the effect of relationship between price variables, perception size, perception of reptation, and quality of service with trust simultaneously and partially. The results of this study indicate that price and reputation perception have no significant effect on trust. While the perception of size and quality of service has a significant influence on trust. Service quality has the greatest influence to trust. The independent variables used in this study contributed 68.4% to the trust of GO-JEK customers.